The heart of winter : a novel - Evison, Jonathan (Dutton, 2025)
"From the author of Again and Again and Small World, a heartwarming novel about a married couple in their eighties, flashing back to tell the story of their lives across their courtship, marriage, children, and long-standing, opposites-attract love. Abe Winter and Ruth Warneke were never meant to be together-at least if you ask Ruth. Yet their catastrophic blind date in college evolved into a seventy-year marriage and a life on a farm on Bainbridge Island with their hens and beloved Labrador Megs. Through the years, the Winters have fallen in and out of lockstep, and out of their haunting losses and guarded secrets, a dependable partnership has been forged. But when Ruth's loose tooth turns out to be something much more malicious, the beautiful, reliable life they've created together comes to a crisis. As Ruth struggles with her crumbling independence, Abe must learn how to take care of her while their three living children question his ability to look after his wife. And once again, the couple has to reconfigure how to be there for each other. In this big-hearted and profound portrait of a marriage, Jonathan Evison explores 70 years of big moments in subtle ways, elegantly braiding the Winters' turbulent history with their present-day battles, showing us how the oddly paired college kids became parents, fell apart and back together, and grew into the Abe and Ruth of today. Endlessly heartwarming and moving, Heart of Winter is a reminder that true love lives in small, everyday moments"--